A high performance nickel-based welding wire and preparation method thereof
By adding specific components to the flux core of the nickel-based welding wire, such as mafic layered bimetal hydroxide, eloite nanotubes and nanolithium titanate, uniformly distribute the molten pool alloy, the nickel-based welding wire is solved. The problem of easy breakage or failure under stress environments has achieved a welding effect with high tensile strength and elongation.
Patent Information
- Application Number
- CN202411115635.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-14
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-08-14
AI Technical Summary
Existing nickel-based welding wires are prone to breaking or failing under high stress and heavy load environments, and it is difficult to maintain high tensile strength and elongation at the same time, limiting their application range.
A high-performance nickel-based welding wire is used, and its flux core includes nickel powder, manganese powder, chromium powder, boron nitride powder, mafic layered bimetallic hydroxide, calcium fluoride powder, elosite nanotubes, hexaboron Raw materials such as cerium chemical and nano-lithium titanate are used in combination to uniformly distribute the molten pool alloy to improve the mechanical properties of the molten metal.
It significantly improves the yield strength, tensile strength and elongation of the deposited metal, ensures that the welded joints maintain stability during long-term use, and overcomes the fracture or failure of existing welding wires under high stress environments.
Smart Images

Figure BDA0004993544850000071 
Figure BDA0004993544850000081 
Figure BDA0004993544850000082
Abstract
Description
Technical Field
[0001] The invention relates to the field of welding materials, and in particular to a high-performance nickel-based welding wire and a preparation method thereof. Background Art
[0002] Nickel-based welding wires have been widely used in the fields of petrochemicals, metallurgy, atomic energy, aviation, etc., due to their excellent corrosion resistance to active gases, caustic media and reducing acid media, as well as their high strength, good plasticity, hot and cold deformation and processing forming properties. However, existing nickel-based welding wires are prone to breakage or failure when facing high stress and heavy load environments, which limits their process performance and application range.
[0003] Specifically, solid welding wire is prone to spatter in all-position welding and is mainly suitable for thin plate welding. In addition, its arc transition method is mostly short-circuit transition, which may lead to insufficient penetration and affect the welding quality. In contrast, flux-cored welding wire can more accurately control the chemical composition of the weld by flexibly adjusting the flux components and proportions, showing a wider range of adaptability. Despite this, nickel-based alloy welding wire is prone to the following problems during the welding process: the deposited metal is prone to thermal cracks, has low impact toughness and tensile strength, and most importantly, it is difficult to maintain high tensile strength and elongation at the same time. These shortcomings limit its scope of application.
[0004] Therefore, the core of the present invention is to develop a high-performance nickel-based welding wire, aiming to significantly improve the mechanical properties and strength of the deposited metal, ensure that the weld joint maintains a high degree of stability during long-term use, and overcome the limitations of existing welding wires. Summary of the invention
[0005] In order to overcome the shortcomings of the prior art, the first purpose of the present invention is to provide a high-performance nickel-based welding wire, in which the molten pool alloy is evenly distributed during the welding process, and the deposited metal can have good yield strength, tensile strength and elongation.
[0006] The second object of the present invention is to provide a method for preparing a high-performance nickel-based welding wire, which has a simple and efficient preparation process.
[0007] The first object of the present invention is achieved by the following technical solution:
[0008] A high-performance nickel-based welding wire comprises a welding skin and a flux core, wherein the flux core comprises the following raw materials in parts by weight: 10-15 parts of nickel powder, 3-6 parts of manganese powder, 5-10 parts of chromium powder, 2-5 parts of boron nitride powder, 3-7 parts of magnesium-iron layered double metal hydroxide, 0.5-1 part of calcium fluoride powder, 0.8-1.4 parts of halloysite nanotubes, 0.2-0.8 parts of cerium hexaboride, and 0.5-1 part of nano lithium titanate.
[0009] Furthermore, it includes welding skin and flux core, and the flux core includes the following raw materials in parts by weight: 12 parts of nickel powder, 5 parts of manganese powder, 7 parts of chromium powder, 3 parts of boron nitride powder, 5 parts of magnesium-iron layered double hydroxide, 0.75 parts of calcium fluoride powder, 1.1 parts of halloysite nanotubes, 0.5 parts of cerium hexaboride, and 0.75 parts of nano lithium titanate.
[0010] Furthermore, the content of each element in the magnesium-iron layered double hydroxide is: C: 6.7wt%, O: 52.2wt%, Mg: 27.2wt%, Fe: 13.9wt%; the size of the magnesium-iron layered double hydroxide is 50-200nm.
[0011] Furthermore, the diameter of the halloysite nanotube is 50-300 nm and the length is 1-10 μm.
[0012] Furthermore, the mass of the flux core accounts for 28-34% of the total mass of the welding wire.
[0013] Furthermore, the particle size of the cerium hexaboride is 1-3 μm; the particle size of the nano lithium titanate is 80-100 nm.
[0014] Nano-lithium titanate is partially decomposed under the action of electric arc, and the titanium element can form oxides and carbides, which together with the undecomposed nano-lithium titanate and cerium hexaboride serve as nucleation particles of the weld structure, play a spontaneous nucleation role, refine the grains of the deposited metal, and improve the low-temperature impact toughness of the deposited metal.
[0015] Cerium hexaboride: Partial decomposition of cerium under the action of the arc can promote the homogenization of the molten pool alloy and help improve the strength of the deposited metal.
[0016] Halloysite nanotubes and MgFe layered double hydroxides: They have more exposed sites, lower diffusion barriers and shorter diffusion paths. By utilizing their tubular and layered structures and adsorption effects, the molten pool alloy is evenly distributed during the welding process, and the deposited metal obtained has better mechanical properties.
[0017] The second object of the present invention is achieved by the following technical solution:
[0018] The above-mentioned method for preparing a high-performance nickel-based welding wire comprises the following steps:
[0019] (1) weighing the raw materials of the drug core according to weight, mixing them evenly, and drying them to obtain the drug core;
[0020] (2) rolling the weld skin to obtain a U-shaped groove; filling the flux core described in step (1) into the U-shaped groove and completely sealing the interface to obtain a U-shaped groove wrapped with the flux core;
[0021] (3) The U-shaped groove wrapped with the flux core is drawn and reduced in diameter to obtain the high-performance nickel-based welding wire.
[0022] Furthermore, the diameter of the welding wire in step (3) is 1.0-2.2 mm.
[0023] Furthermore, the weld skin in step (2) is made of Inconel 625 steel strip.
[0024] Furthermore, the Inconel625 steel strip: C≤0.10, Si≤0.50, Mn≤0.5, P≤0.015, S≤0.015, Cr: 20.0-23.0, Al≤0.40, Ti≤0.40, Fe≤5.00, Co≤1.00, Ni balance.
[0025] Furthermore, the drying temperature in step (1) is 100-150° C., and the drying time is 2-3 hours.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] The present invention improves the composition of the flux core, and the added nano lithium titanate can improve the low temperature impact toughness of the deposited metal, and the cerium hexaboride can help improve the strength of the deposited metal. Halloysite nanotubes and magnesium-iron layered double metal hydroxides make the molten pool alloy evenly distributed during the welding process, and the obtained deposited metal has good mechanical properties. The above components are used in combination to effectively solve the problems of poor mechanical properties and low strength of the deposited metal. DETAILED DESCRIPTION
[0028] The technical scheme of the present invention is further explained below in conjunction with specific embodiments, comparative examples and test examples. In the following embodiments, comparative examples and test examples, the raw materials and preparation methods used are conventional materials and techniques in the art unless otherwise specified.
[0029] The Inconel625 steel strip described in the present invention has the following characteristics: C≤0.10, Si≤0.50, Mn≤0.5, P≤0.015, S≤0.015, Cr: 20.0-23.0, Al≤0.40, Ti≤0.40, Fe≤5.00, Co≤1.00, and Ni as a remainder.
[0030] The content of each element in the magnesium-iron layered double metal hydroxide is: C: 6.7wt%, O: 52.2wt%, Mg: 27.2wt%, Fe: 13.9wt%, and the size of the magnesium-iron layered double metal hydroxide is 50-200nm.
[0031] The halloysite nanotube has a diameter of 50-300 nm and a length of 1-10 μm.
[0032] The nickel powder contains Ni≥99.8%, C≤0.02%, S≤0.003%, and P≤0.01%, and the particle size of the nickel powder is 150 meshes.
[0033] The purity of the manganese powder is ≥99.9%, and the particle size is 200-300 meshes.
[0034] The chromium powder contains Cr≥99.9%, Fe≤0.05%, Si≤0.015%, Al≤0.01%, Mn≤0.003%, C≤0.02%, S≤0.005%, P≤0.002%, Sn≤0.001%, N≤0.002%, Pb≤0.0005%, and O≤0.05%, and the particle size of the chromium powder is 80-150 meshes.
[0035] The boron nitride powder has a purity of ≥99.95% and an average particle size of 200 nm.
[0036] The cerium hexaboride has a purity of ≥99.5% and a particle size of 1-3 μm.
[0037] The particle size of the calcium fluoride powder is 200-300 meshes.
[0038] The particle size of the nano lithium titanate is 80-100 nm.
[0039] Example 1
[0040] A high-performance nickel-based welding wire consists of a welding skin and a flux core, wherein the welding skin is an Inconel 625 steel strip, and the flux core comprises the following raw materials in parts by weight: 12 parts of nickel powder, 5 parts of manganese powder, 7 parts of chromium powder, 3 parts of boron nitride powder, 5 parts of magnesium-iron layered double metal hydroxide, 0.75 parts of calcium fluoride powder, 1.1 parts of halloysite nanotubes, 0.5 parts of cerium hexaboride, and 0.75 parts of nano lithium titanate.
[0041] A method for preparing a high-performance nickel-based welding wire comprises the following steps:
[0042] (1) Weighing the raw materials of the above-mentioned drug core according to weight, placing them in a powder mixer and mixing them evenly, and drying them in a vacuum dryer at 135° C. for 2.5 hours to obtain a drug core;
[0043] (2) removing grease from the surface of the Inconel 625 steel strip with alcohol, bending the weld skin into a U-shaped groove by a flux-cored wire forming machine, filling the flux core described in step (1) into the U-shaped groove, and then completely sealing the interface thereof, rolling it into an O-shape, and obtaining a U-shaped groove wrapped with the flux core;
[0044] (3) The U-shaped groove wrapped with the flux core is drawn and reduced in diameter by a drawing die to obtain a product, namely the nickel-based welding wire of the present invention, with a diameter of 1.5 mm.
[0045] Example 2
[0046] A high-performance nickel-based welding wire consists of a welding sheath and a flux core, wherein the welding sheath is an Inconel 625 steel strip, and the flux core comprises the following raw materials in parts by weight: 10 parts of nickel powder, 3 parts of manganese powder, 5 parts of chromium powder, 2 parts of boron nitride powder, 3 parts of magnesium-iron layered double metal hydroxide, 0.5 parts of calcium fluoride powder, 0.8 parts of halloysite nanotubes, 0.2 parts of cerium hexaboride, and 0.5 parts of nano-lithium titanate.
[0047] A method for preparing a high-performance nickel-based welding wire comprises the following steps:
[0048] (1) Weigh the raw materials of the above-mentioned drug core according to weight, mix them evenly in a powder mixer, and dry them in a vacuum dryer at 100° C. for 3 hours to obtain a drug core;
[0049] (2) removing grease from the surface of the Inconel 625 steel strip with alcohol, bending the weld skin into a U-shaped groove by a flux-cored wire forming machine, filling the flux core described in step (1) into the U-shaped groove, and then completely sealing the interface thereof, rolling it into an O-shape, and obtaining a U-shaped groove wrapped with the flux core;
[0050] (3) The U-shaped groove wrapped with the flux core is drawn and reduced in diameter by a drawing die to obtain a product, namely the nickel-based welding wire of the present invention, with a diameter of 1.0 mm.
[0051] Example 3
[0052] A high-performance nickel-based welding wire consists of a welding sheath and a flux core, wherein the welding sheath is an Inconel 625 steel strip, and the flux core comprises the following raw materials in parts by weight: 15 parts of nickel powder, 6 parts of manganese powder, 10 parts of chromium powder, 5 parts of boron nitride powder, 7 parts of magnesium-iron layered double hydroxide, 1 part of calcium fluoride powder, 1.4 parts of halloysite nanotubes, 0.8 parts of cerium hexaboride, and 1 part of nano lithium titanate.
[0053] A method for preparing a high-performance nickel-based welding wire comprises the following steps:
[0054] (1) Weigh the raw materials of the above-mentioned drug core according to weight, mix them evenly in a powder mixer, and dry them in a vacuum dryer at 150° C. for 2 h to obtain a drug core;
[0055] (2) removing grease from the surface of the Inconel 625 steel strip with alcohol, bending the weld skin into a U-shaped groove by a flux-cored wire forming machine, filling the flux core described in step (1) into the U-shaped groove, and then completely sealing the interface thereof, rolling it into an O-shape, and obtaining a U-shaped groove wrapped with the flux core;
[0056] (3) The U-shaped groove wrapped with the flux core is drawn and reduced in diameter through a drawing die to obtain a product, namely the nickel-based welding wire of the present invention, with a diameter of 2.2 mm.
[0057] Comparative Example 1
[0058] This comparative example 1 provides a high-performance welding wire, which differs from Example 1 in that 7 parts of magnesium-iron layered double metal hydroxide in the flux core raw material are replaced by 3 parts of magnesium powder and 4 parts of iron powder.
[0059] This comparative example also provides a method for preparing a high-performance nickel-based welding wire. Similar to Example 1, the diameter of the prepared welding wire is 1.5 mm.
[0060] Comparative Example 2
[0061] This comparative example 2 provides a high-performance welding wire, which is different from the example 1 in that the cerium hexaboride in the flux core raw material is omitted.
[0062] This comparative example also provides a method for preparing a high-performance nickel-based welding wire. Similar to Example 1, the diameter of the prepared welding wire is 1.5 mm.
[0063] Comparative Example 3
[0064] Comparative Example 3 provides a high-performance welding wire, which differs from Example 1 in that the nano-lithium titanate in the core material is omitted.
[0065] This comparative example also provides a method for preparing a high-performance nickel-based welding wire. Similar to Example 1, the diameter of the prepared welding wire is 1.5 mm.
[0066] Comparative Example 4
[0067] Comparative Example 4 provides a high-performance welding wire, which differs from Example 1 in that the halloysite nanotubes in the flux core raw material are replaced with halloysite.
[0068] This comparative example also provides a method for preparing a high-performance nickel-based welding wire. Similar to Example 1, the diameter of the prepared welding wire is 1.5 mm.
[0069] Test Example 1
[0070] 1. The nickel-based welding wires prepared in Examples 1-3 and Comparative Examples 1-4 were selected as welding materials, and the nickel-based welding wires were butt-welded to Incoloy 800H base metal. The welding processes of the nickel-based welding wires prepared in Examples 1-3 and Comparative Examples 1-4 are shown in Table 1. The mechanical properties of the deposited metal were tested with reference to GB / T 2652-2008 "Weld and Deposited Metal Tensile Test Method" and "Welded Joint Impact Test Method", and the results are shown in Table 2.
[0071] Table 1
[0072] Welding methods Welding current (A) Welding voltage(V) Semi-automatic TIG welding with wire filling 200-280 13-20 Current polarity Welding speed (m / min) Wire feeding speed (m / min) DC / positive connection SP 0.5-0.6 4-6 Gas flow rate (L / min) Interlayer temperature (℃) Protective gas 15-20 <100 Argon
[0073] Table 2
[0074]
[0075]
[0076] It can be seen from the test results in Table 2 that the yield strength, tensile strength and elongation of the deposited metal components of the nickel-based welding wires of Examples 1-3 of the present invention are much higher than those of Comparative Examples 1-4.
[0077] Compared with Example 1, Comparative Example 4 replaces the halloysite nanotubes with halloysite, and the mechanical properties of the deposited metal are all reduced; Comparative Example 1 replaces the magnesium-iron layered double hydroxide with magnesium powder and iron powder, and the mechanical properties of the deposited metal are the worst; Comparative Example 2 omits the cerium hexaboride in the flux core, and Comparative Example 3 omits the nano-lithium titanate, and its tensile strength, yield strength and elongation are all less than those of Comparative Example 4. This is because the nano-lithium titanate is partially decomposed under the action of the arc, and the titanium element can form oxides and carbides, which together with the undecomposed nano-lithium titanate and cerium hexaboride serve as nucleation particles of the weld structure, play a spontaneous nucleation role, refine the grains of the deposited metal, and can improve the low-temperature impact toughness of the deposited metal, extending its service life and safety.
[0078] Test Example 2
[0079] The nickel-based welding wires prepared in Examples 1-3 and Comparative Examples 1-4 were selected as welding materials, and the nickel-based welding wires were butt-welded to Incoloy 800H base metal. Five representative test points were selected on the surface of the deposited metal sample, and the hardness of the deposited metal was tested with reference to GB / T 2654 “Test method for hardness of welded joints”. The test results are shown in Table 3.
[0080] Table 3
[0081]
[0082]
[0083] From the results in Table 3, it can be seen that the hardness of the deposited metals of Examples 1-3 of the present invention is relatively high, at about 67%, which is significantly higher than that of Comparative Examples 1-4 and meets the hardness requirements of the deposited metals.
[0084] The above-mentioned embodiments are only preferred embodiments of the present invention and cannot be used to limit the scope of protection of the present invention. Any non-substantial changes and substitutions made by technicians in this field on the basis of the present invention shall fall within the scope of protection required by the present invention.
Claims
1. A high performance nickel-based welding wire, characterized in that: The invention comprises welding skin and flux core, wherein the flux core is composed of the following raw materials in parts by weight: 10-15 parts of nickel powder, 3-6 parts of manganese powder, 5-10 parts of chromium powder, 2-5 parts of boron nitride powder, 3-7 parts of magnesium-iron layered double metal hydroxide, 0.5-1 parts of calcium fluoride powder, 0.8-1.4 parts of halloysite nanotubes, 0.2-0.8 parts of cerium hexaboride, and 0.5-1 parts of nano lithium titanate; The content of each element in the magnesium-iron layered double metal hydroxide is: C: 6.7wt%, O: 52.2wt%, Mg: 27.2wt%, Fe: 13.9wt%; the size of the magnesium-iron layered double metal hydroxide is 50-200nm.
2. A high performance nickel-based welding wire according to claim 1, characterized in that: The invention comprises welding skin and flux core, wherein the flux core is composed of the following raw materials in parts by weight: 12 parts of nickel powder, 5 parts of manganese powder, 7 parts of chromium powder, 3 parts of boron nitride powder, 5 parts of magnesium-iron layered double metal hydroxide, 0.75 parts of calcium fluoride powder, 1.1 parts of halloysite nanotubes, 0.5 parts of cerium hexaboride and 0.75 parts of nano lithium titanate.
3. A high performance nickel-based welding wire according to claim 1, characterized in that: The diameter of the halloysite nanotube is 50-300nm and the length is 1-10µm.
4. A high performance nickel-based welding wire according to claim 1, characterized in that: The mass of the flux core accounts for 28-34% of the total mass of the welding wire.
5. A high performance nickel-based welding wire according to claim 1, characterized in that: The particle size of the cerium hexaboride is 1-3 μm; the particle size of the nano lithium titanate is 80-100 nm.
6. A method for preparing a high performance nickel-based welding wire according to any one of claims 1 to 5, characterized in that: The following steps are involved: (1) Weighing the raw materials of the above-mentioned drug core according to weight, mixing them evenly, and drying them to obtain the drug core; (2) rolling the weld skin to obtain a U-shaped groove; filling the flux core described in step (1) into the U-shaped groove and completely sealing the interface to obtain a U-shaped groove wrapped with the flux core; (3) The U-shaped groove wrapped with the flux core is drawn and reduced in diameter to obtain the high-performance nickel-based welding wire.
7. The method for preparing a high-performance nickel-based welding wire according to claim 6, characterized in that: The diameter of the welding wire in step (3) is 1.0-2.2 mm.
8. The method for preparing a high performance nickel-based welding wire according to claim 6, characterized in that: The weld skin in step (2) is made of Inconel 625 steel strip.
9. The method for preparing a high-performance nickel-based welding wire according to claim 6, characterized in that: The drying temperature in step (1) is 100-150°C and the drying time is 2-3h.
Citation Information
Patent Citations
Flux core steel strip welding wire
CN108723634A
Nonaqueous electrolyte battery inorganic particles and nonaqueous electrolyte battery
CN108780914A